Democratic breakdown and the decline of the Russian military - Barany, Zoltan D. (Princeton University Press, 2007)
Why have Russian generals acquired an important political position since the Soviet Union's collapse while at the same time the effectiveness of their forces has deteriorated? Why have there been no radical defense reforms in Russia since the end of the cold war, even though they were high on the agenda of the country's new president in 2000? Democratic Breakdown and the Decline of the Russian Military explains these puzzles as it paints a comprehensive portrait of Russian military politics. Zoltan Barany identifies three formative moments that gave rise to the Russian dilemma.